ACINETOBACTER INFECTIONS AS AN EMERGING THREAT IN INTENSIVE CARE UNITS - Tahseen, Uzma; Talib, Muhammad Tahseen (Journal of Ayub Medical College Abbottabad, 2015)
Background: Nosocomial infections caused by Acinetobacter species (Spp.) is an emerging threat in health care setups especially intensive care units (ICU). The objective of this observational study was to determine the pattern of Acinetobacter infections and its association with length of stay in patients admitted to our medical ICU from January to August 2011. Methods: All patients above 16 years of age with stay of more than 48 hours were checked for any development of new infections not present or incubating at the time of admission. Nosocomial infections were documented in the light of clinical findings and lab results. Data was analysed using statistical software SPSS 15.0. Results: A total of 146 patients had a stay of at least 48 hours; frequency of nosocomial infection was 30.8% out of which 57.8% were Acinetobacter infections. Respiratory system was most commonly involved. Acinetobacter Spp showed high resistance (96.2%) to penicillins, cephalosporins and even extended spectrum antibiotics including carbepenems, quinolones and piperacillin plus tazobactam. Extended drug resistance was seen in 92.3% isolates; while we found high susceptibility to tigecycline (88.5%) and polymyxins (100%). Acinetobacter Spp. infected patients had mean length of stay (LOS) of 12.92 days when compared to patients with other nosocomial infections and no infection with mean LOS of 7.05 days (p=0.05) and 4.86 days (p=0.00) respectively. Conclusions: Acinetobacter Spp infections increase with longer duration of stay in ICU. Emergence of multi-drug and extended-drug resistant Acinetobacter Spp is alarming and overwhelming at this rate for already stretched out health system with its economic and health implications. Keywords: Acinetobacter, medical ICU, nosocomial Infection, multi-drug resistant, hospital acquired infection